PENGARUH DUKUNGAN SEKOLAH TERHADAP MINAT SISWA UNTUK MENGIKUTI KEGIATAN EKSTRAKURIKULER DI SDIT AL-IZZAH KOTA SERANG - Atiah , Siti; Sabri; Farhurohman, Oman (ATTA`DIB, 2024)
This research aims to test how much influence school support has on students' interest in participating in extracurricular activities at SDIT Al-Izzah Serang City. Students' interest in participating in extracurricular activities is very important because it is the initial encouragement for students to develop interests and talents. School support, which includes the provision of facilities, competent supervisors, programmed activities, as well as motivation and appreciation, plays an important role in increasing student interest. The research method used is quantitative correlational with simple linear regression analysis. Data was collected through a questionnaire distributed to 51 class IV students. Research results show that there is a significant positive influence between school support and students' interest in participating in extracurriculars. As much as 43.5% of student interest is influenced by school support. These findings indicate that increasing school support can be an effective strategy to increase student interest in extracurricular activities. Schools need to pay attention to the quality of facilities, accompanying competence, and provide more optimal motivation and appreciation to students. The results of this research are expected to provide an understanding of the factors that can affect students' interest in participating in extracurriculars. The results of this research can be a consideration for schools, especially SDIT Al-Izzah, in an effort to improve the quality of extracurricular programs and encourage students to participate more actively.